The “Sleeper” plate: A technical note - Muayad Kadhim; Ahmed I Hammouda; John E Herzenberg (Journal of Limb Lengthening & Reconstruction, 2019)
Context: A tension band plate (TBP) for guided growth of angular deformity is typically removed after the deformity is corrected to prevent overcorrection. After TBP removal, rebound deformity may occur, necessitating reinsertion of a new TBP. Aims: This study aims to describe a minimally invasive technique for partial removal of TBP to deactivate the TBP when correction is achieved. The technique also allows minimally invasive reactivation of the construct when desired. Settings and Design: This is retrospective case series study. Subjects and Methods: The surgery consists of removing the metaphyseal screw only and keeping the plate and the epiphyseal screw. The procedure is done through a 1-cm incision with fluoroscopy. The metaphyseal edge of the plate is elevated off the bone to break the seal between it and the bone, to prevent tethering. Bone wax is injected in the empty plate hole to prevent bone ingrowth, as this could also cause re-tethering. In case of a subsequent rebound deformity, the metaphyseal screw may be re-inserted percutaneously to reactivate (“wake-up”) the “sleeper plate”. Statistical Analysis Used: Descriptive analysis. Results: The sleeper plate technique was done in eight patients (three males and five females). Four patients had genu valgum and four had genu varum. Mean age at surgery was 11 years (7–14 years). Metaphyseal screw removal was done in a mean period of 14 months (range from 7.4 to 22 months) after the index procedure. Rebound of the deformity happened in three patients and required plate reactivation by reinsertion of the metaphyseal screw. Conclusion: The sleeper plate technique is a minimally invasive procedure and can be an alternative to the removal of the whole TBP construct if the patient is skeletally immature with a risk of deformity rebound. Level of Evidence: IV